Endothelial growth factor receptor inhibitors in recurrent metastatic cancer of the head and neck. (5th November 2015) - Misiukiewicz, Krzysztof; Dang, Rajan P.; Parides, Michael; Camille, Nadia; Uczkowski, Helen; Sarlis, Nicholas J.; Posner, Marshall
Abstract: Targeted therapy has become an important new class of therapeutic agents used in squamous cell carcinoma of the head and neck (SCCHN). Among them epidermal growth factor receptor (EGFR) inhibitors have been studied the most. Today, two classes of EGFR inhibitors are routinely used in the clinic; anti‐EGFR monoclonal antibodies and small‐molecule inhibitors of the EGFR tyrosine kinase activity. These agents have been used clinically in the recurrent metastatic (R/M) settings but only cetuximab has reached a regulatory approval. Current research is focused on innovative compound design, predictive biomarker discovery, and combination strategies in order to overcome resistance. Efforts should also be focused on endpoints other than overall survival, which is the current gold standard, such as surrogate endpoints. This article summarizes the clinical evidence of the anticancer activity of EGFR inhibitors in patients with R/M SCCHN, and analyzes the current, controversial clinical issues with respect to their interpretation. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E2221–E2228, 2016